Gamma spectrometry technique for the determination of residence time in Submarine Groundwater Discharges - Eleftheriou, G.; Tsabaris, C.; Patiris, D. L.; Androulakaki, E.; Kokkoris, M.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
The evaluation of time period that meteoric water remains in the ground (residence time) before exiting in the open sea can be a valuable information for the submarine groundwater discharges (SGD) in the costal zones. Coastal waters contain elevated dissolved activities of radium isotopes compared to the open ocean, where excess activities are zero. Lately it has been shown by Moore et al., that residence time can be estimated by a model based on radium radioisotopes ratio reduction throughout the coast. However the standard methods for the estimation of radium isotopes concentration in the water are sophisticated, time consuming or require big amount of sample. Hereby, a method based on the direct gamma ray spectrometry of untreated water samples from coastal areas is applied to determine the residence time of the SGD. Efficiency calibration of the spectrometry set up has been performed for two different volumetric sample geometries, using 152Eu/154Eu solution as reference source. In order to ensure the reliability of the method, the background courting rate magnitude and variance through time have been defined for the radioisotopes of interest. Additionally, the minimum detectible activity (MDA) of the measuring system was determined, in Becquerel per cubic meter, as a function of energy in water samples. The developed method was applied and validated for water samples from the submarine spring in Stoupa Bay, southwestern Peloponnesus. The defined residence time varies from 3 to 6 days, being in good agreement with the results of the standard geological pigment-tracer method.